Divergence in spatial patterns of leaf stoichiometry between native and non-native plants across coastal wetlands - Zhang, Youzheng; Guo, Yaolin; Wang, Hui; Li, Niu; Xu, Hengtao; Zhang, Dongrong; Qian, Jian; Hu, Yukun (Frontiers in Marine Science, 2024)
The spatial pattern of leaf stoichiometry is critical in predicting plant palatability and ecosystem productivity and nutrient cycling rates and thus is a major focus of community ecological research. Coastal wetlands as vital blue carbon ecosystems, with high possibility to be vulnerable to plant invasion, studies focused on stoichiometry and its pattern are important to unveil the elements cycling process. However, previous studies have mainly focused on stoichiometry in terrestrial ecosystems, there are few studies conducted on coastal wetland ecosystems, especially the studies that compare leaf stoichiometry between native and non-native plants in coastal wetlands. In this study, we compared the latitudinal patterns of leaf nutrient contents and their stoichiometric ratios between native and non-native plant species across coastal wetland ecosystems and investigated whether leaf stoichiometric patterns were driven by climatic factors. We used a compiled global data set of 954 records to conduct a systematic meta-analysis. The results showed that there were significant differences in latitudinal patterns of leaf carbon (C) and nitrogen (N) contents and C:N ratio between native and non-native species, as well as significant differences in leaf C, N, and phosphorus (P) contents. For native species, we found significant latitudinal patterns in leaf C, N, and P contents and C:N and C:P ratios, whereas for non-native species, we found significant latitudinal patterns in leaf N content and C:P and N:P ratios. Mean annual temperature of the data collection site was a significant predictor of leaf stoichiometry of native plants but only of leaf N content and C:P ratio of non-native plants. Thus, we demonstrated spatial heterogeneity in leaf stoichiometries between native and non-native plants in coastal wetlands, indicating that such differences should be emphasized in future biogeochemical models and plant-herbivore interaction studies owing to the important role of wetland plants in global C, N, and P cycles. Our findings increase understanding of plant-related nutrient and elements cycling in coastal wetlands, as well as improve predictions of plant growth rates and vegetation productivity across large scales under plant invasion scenarios.